A Facile One‐Step Synthesis of Fe‐Doped g‐C3N4 Nanosheets and Their Improved Visible‐Light Photocatalytic Performance. Issue 9 (20th April 2017) - Gao, Jingtian; Wang, Yun; Zhou, Shijian; Lin, Wei; Kong, Yan
Abstract: A simple one‐step pyrolysis process (compared with the routine method of liquid exfoliation and impregnation) was designed to synthesize Fe‐doped graphitic carbon nitride (g‐C3 N4 ) nanosheets with NH4 Cl as dynamic gas template and FeCl3 as the Fe source. Results of XPS and DRS indicated that the Fe species might exist at the state of Fe 3+ and form Fe−N bonds with N atoms, thereby expanding visible light absorption regions and reducing the band gap of g‐C3 N4 nanosheets. Doping certain amounts of Fe could promote the exfoliation and further increase the specific surface area, while excessive Fe might break the sheet structure. The specific surface area of the optimized Fe‐doped g‐C3 N4 nanosheets reached 236.52 m 2 g −1, which was 2.5 times higher than that of g‐C3 N4 nanosheets. Among various photocatalysts prepared, the sample (0.5 wt % FeCl3 ) exhibited maximum photocatalytic performance in degradation of Methylene Blue and water splitting under visible light irradiation. The degradation rate of MB was about 1.4 and 1.7 times higher than that of pure g‐C3 N4 nanosheets and bulk g‐C3 N4, respectively. The H2 production rate was 536 μmol h −1 g −1, which was 1.8 and 6 times higher than that of pure g‐C3 N4 nanosheets and bulk g‐C3 N4, separately. Abstract : Visibly better : A facile one‐step pyrolysis process was developed to synthesize iron‐doped graphitic carbon nitride nanosheets. The sample with 0.5 wt % FeCl3 exhibited the best photocatalytic performance in the degradation of Methylene Blue and water splitting under visible light irradiation.